PEOPLE’S PEDAGOGY - METHODS OF NATIONAL EDUCATION THROUGH TRADITIONS - Turkmenbaeva Khurshida Gaypnazarovna (International Journal of Innovations in Engineering Research and Technology, 2021)
This article ehamines the origin and uniqueness of some traditions of the Karakalpak people, which have been formed over several centuries, which are also found in other peoples.